Remediation of Pb-contaminated soil using P-engineered biochar and biomonitoring employing bioindicators (2022)
Soil contamination by lead can result from different anthropogenic sources such as lead-based paints, gasoline, pesticides, coal burning, mining, among others. The aim of this work is to use biochar and activated biochar loaded with phosphorus to evaluate their potential remediation of lead in an entisol-type soil. For this, biochar was obtained at different temperatures (450, 500, 550 and 600 ºC), then a part was activated and placed in different proportions in the soil (0.5, 1.0 and 2.0%). The bioavailability of P and Pb in the soil has been determined over time, and at 45 days the effect of P-engineered biochar in the soil has been evaluated using different bioindicators. Activated P-engineered biochar produced at 500 ºC has been found to present the best conditions for soil Pb remediation.